Effectiveness of Promotional Strategy of Ncell Mobile Service in Nepal - Tamang, Samir (Nepalese Journal of Economics, 2025)
This study examines the effectiveness of promotional strategy of Ncell mobile service in Nepal. Customer preference is the dependent variable. The selected independent variables are offers, TV advertisement, hoarding board, celebrity endorsements, and campaigns. The primary source of data is used to assess the opinions of respondents regarding offers, TV advertisement, hoarding board, celebrity endorsements, campaigns, and customer preference. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of effectiveness of promotional strategy of Ncell mobile service in Nepal The study showed a positive impact of TV advertisement on customer preference. It indicates that positive TV advertisements leads to change in customer preference. Similarly, the study showed a positive impact of hoarding board on customer preference. It indicates that an attractive hoarding board leads to change in customer preference. Likewise, the study showed a positive impact of celebrity endorsement on customer preference. It indicates that higher the celebrity branding or celebrity advertising, higher would be the customer preference. Further, the study revealed a positive impact of campaigns on customer preference. It indicates that campaigns enhance the customer preference towards the brand. In addition, the study showed a positive impact of offers on customer preference. It indicates that innovative and attractive offers enhance the customer preference towards the products.